New Frontiers in Fibers: Innovative and Emerging Research on the Gut Microbiome and Bone Health. (3rd April 2017) - Wallace, Taylor C.; Marzorati, Massimo; Spence, Lisa; Weaver, Connie M.; Williamson, Patricia S.
ABSTRACT: The complex interactions between the diet, gut microbiome, and host characteristics that provide a functional benefit to the host are an area of great interest and current exploration in the nutrition and health science community. New technologies are available to assess mechanisms that may explain these functional benefits to the host. One emerging functional benefit from changes in the gut microbiome is increased calcium absorption, increased calcium retention, and improved indices of bone health. Prebiotic fibers enhance microbial fermentation in the gut, providing an ecological advantage to specific nonpathogenic bacteria that have the ability to modify an individual's metabolic potential. Fermentation of fibers also leads to increased production of short-chain fatty acids. These changes have been positively correlated with increased calcium absorption in humans and increased bone density and strength in animal models. Dietary fibers may offer an additional means to enhance calcium absorption with the possibility of stimulating the gut microbiome to ultimately influence bone health. This hot topic perspectives piece reviews innovative technologies that can be used to assess the impact of prebiotic fibers on the gastrointestinal tract (GIT) as well as the potential mechanisms that may explain their health effects on bone. Validated in vitro models used to measure alterations in the gut microbiome, as well as animal and clinical studies assessing the role of prebiotic fibers on calcium absorption and bone indices through alternations in the gut microbiome, are presented.